Effectiveness of Sewing Skills in Enhancing Customer Satisfaction at Andela Tailor, Way Jepara, East Lampung - Fauzi Fauzi; Susi Sulastri; Muhsinin Muhsinin (Utan Kayu Publishing, 2024)
In the modern era, Indonesian society, especially women, continues to follow the latest fashion trends, often seeking the services of tailors to create garments according to their specifications. The quality of tailoring services is crucial in meeting consumer expectations and staying competitive in the market. This study aims to analyze the influence of sewing skills on consumer satisfaction at Penjahit Andela in Way Jepara, Lampung Timur. The research employs a simple linear regression analysis with sewing skills as the independent variable and consumer satisfaction as the dependent variable. The study involved 100 respondents, selected through accidental sampling. The results show a significant relationship between sewing skills and consumer satisfaction, with an R-value of 0.743, indicating a strong correlation. The R square value of 0.552 suggests that 55.2% of consumer satisfaction is influenced by sewing skills, while the remaining 44.8% is affected by other factors not examined in this study. The hypothesis stating that